2000
DOI: 10.1017/s0266462300103149
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE LEARNING CURVE IN HEALTH TECHNOLOGIES A Systematic Review

Abstract: Objective: We reviewed and appraised the methods by which the issue of the learning curve has been addressed during health technology assessment in the past. Method: We performed a systematic review of papers in clinical databases (BIOSIS, CINAHL, Cochrane Library, EMBASE, HealthSTAR, MEDLINE, Science Citation Index, and Social Science Citation Index) using the search term "learning curve." Results: The clinical search retrieved 4,571 abstracts for assessment, of which 559 (12%) published articles were eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 51 publications
5
140
0
1
Order By: Relevance
“…The surgeons in that study [25] accumulated experience with PAO by scrubbing as first assistant during residency and by visiting with the originator of the technique. However, we did find an inverse relationship between experience (number of PAO procedures performed) and operative time, a possible surrogate measure of surgical performance and learning curve [22]. This is consistent with the study by Davey and Santore [8] that reported a statistically significant reduction in surgical time from 3 hours 48 minutes to 3 hours 24 minutes.…”
Section: Discussionsupporting
confidence: 92%
“…The surgeons in that study [25] accumulated experience with PAO by scrubbing as first assistant during residency and by visiting with the originator of the technique. However, we did find an inverse relationship between experience (number of PAO procedures performed) and operative time, a possible surrogate measure of surgical performance and learning curve [22]. This is consistent with the study by Davey and Santore [8] that reported a statistically significant reduction in surgical time from 3 hours 48 minutes to 3 hours 24 minutes.…”
Section: Discussionsupporting
confidence: 92%
“…Ramsay et al 16 conducted a study in which they searched the medical literature to ascertain how learning curves are evaluated. In searching multiple databases, they found 4571 abstracts that contained the phrase "learning curve."…”
Section: Discussionmentioning
confidence: 99%
“…15 Commonly data are split into arbitrary groups and the means compared by chi-squared test or ANOVA. Some studies had data displayed graphically with no statistical analysis.…”
Section: Statistical Evaluation Of Learning Curvesmentioning
confidence: 99%